THE EFFECT OF PARENTS SOCIAL SUPPORT ON STUDENT SELF IMAGE - Marlia Tyas Asih; Dwi Endarso (Akademika : Jurnal Teknologi Pendidikan, 2023)
This study aims to examine the effect of parental social support on students self image. This research is a quantitative research with a descriptive research type. The population in the study was class VIII students at SMP Negeri 81 Jakarta with a total of 252 students. From this population, samples were taken using the Random Sampling technique which resulted in a sample of 170 students. The technique of collecting data in this study uses a questionnaire. The data is then tested for validity and reliability, categorized, then data analysis is the T test (Partial). Based on the results of the study, it was stated that the social support of parents of class VIII students at SMP Negeri 81 Jakarta was in the moderate category with a percentage of 60.3%. While self image in class VIII SMP Negeri 81 Jakarta is also in the moderate category with a percentage of 62, 4% and the results of the Partial T Test for the significance value of the Coefficient table were obtained by Sig. 0.000 which means 0.000<0.05. And the coefficient of determination (R Square) is 0.321 which implies that the effect is 30.1% and the remaining 63.9% is influenced by other factors. The conclusion in this study is that there is a significant influence of parental social support on the self image of class VIII students at SMP Negeri 81 Jakarta.